Perception And Readiness Of Pharmacy Faculty Students in Surakarta Central Java About Interprofessional Education - Mutmainah, Nurul; Anisa Rachma Priyastiningrum; Nurus Hasta Rani (Pharmacon: Jurnal Farmasi Indonesia, 2024)
Interprofessional Education (IPE) is an important approach in health education to prepare students to work collaboratively in interprofessional teams in clinical practice. This study aims to determine the perception and readiness of Interprofessional Education among students of the Faculty of Pharmacy in Surakarta, Central Java and to determine the factors that influence differences in perception and readiness. This study used descriptive and cross sectional design. The population used was Pharmacy undergraduate students and pharmacist professional students. Sampling using purposive sampling technique. Measurement of perception using the IEPS (Interprofessional Education Perception Scale) questionnaire, while measuring readiness using the Readiness for Interprofessional Learning Scale (RIPLS) questionnaire. Data were analyzed using the Kruskall Wallis test. Of the 219 respondents, 87.2% were female, 81.2% were undergraduate students, 72.1% had one IPE experience. From the results of measuring perceptions, 96.7% had good perceptions and 3.2% had moderate perceptions. While from the measurement of readiness it was found that 99.5% had high readiness and 0.5% moderate readiness. From the IEPS results, the value of p=0.304 (gender), p=0.909 (student batch) and p=0.699 (IPE experience) was obtained and results on RIPLS obtained a value of p=0.122 (gender), p=0.58 (student batch) and p=0.693 (IPE experience) so it can be concluded that there are no differences in perception and readiness between gender, batch and IPE experience.